ETIOLOGICAL STRUCTURE OF INFLUENZA AND OTHER ARVI IN ST. PETERSBURG DURING EPIDEMIC SEASONS 2012-2016 - M. M. Pisareva; V. A. Eder; Zh. V. Buzitskaya; T. D. Musaeva; V. S. Afanaseva; A. A. Go; E. A. Obraztsova; V. F. Sukhovetskaya; A. B. Komissarov (Вопросы вирусологии, 2018)
The etiological structure of influenza and other acute respiratory viral infections including their rate of incidence in St. Petersburg and Leningrad region during 4 epidemic seasons has been studied. Seasonality of some respiratory viruses was shown and peaks of circulation of RSV, adenovirus, parainfluenza viruses, rhinovirus, bocavirus, metapneumovirus and coronavirus were marked. The interference of influenza A viruses and RSV, RSV and rhinoviruses was highlighted. A high incidence of adenovirus infection in organized communities and RSV infection in children was revealed.